FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA STAF ADMINISTRASI RUANGAN DI RSUD K.R.M.T. WONGSONEGORO KOTA SEMARANG - Nur Saidah; Ekawati Ekawati; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Stress occurs in almost all workers, both at the executive and lower levels. Work stress occurs mostly in individuals who work in the service field. Hospital is one of the community service centers who has responsibility to provide maximum health care to its patients. The purpose of this research is to analyze the factors related to work stress on hospital administration staff in the hospital. This research is a quantitative research with descriptive research method and cross sectional approach. The population of this study is the room administrative staff that amounted to 34 people and the sampling method is total sampling. The dependent variable in this research is job stress and the independent variables are mental work load, physical workload, physical condition of work environment, work routine, individual role in work/ organization, career development, and personality type. Data collection in this study was conducted using questionnaires and also observation to the respondent’s activities. The data were analyzed using Chi-Square correlation test. The result of the statistical test shows that there is a relationship between mental workload, work routine, career development and personality type with work stress on the room administrative staff. While there is no relationship between the physical workload, the physical condition of the work environment, and individual role in work/ organization with work stress on the room administrative staff. Hospital should organize relaxation activities such as character building training and insert some materials about stress management, create a program that can display video about stretching in the computer’s worker at certain hours, and organizing career development training activities.